Tonga : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Tonga. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
Tonga's nascent economic recovery following Tropical Cyclone Harold and border closures in early 2020 has been severely disrupted by a double blow from the Hunga Tonga-Hunga Ha'apai volcanic eruption and the first local outbreak of COVID-19 at the start of 2022. The authorities are augmenting reconstruction and restoration efforts, with support from the international community. Real GDP is projected to contract by 1.9 percent in FY2022 (July 2021-June 2022), before rebounding by 3.2 percent in FY2023 with a gradual reopening of international borders.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Tonga